The Effect of Empowerment Program on Health-Related Quality of Life of Type 1 Diabetic Adolescents - Muhammad Kamel Hassan; Fatemeh Farazi; Aramesh Rezaeian; Haider Al-Asadi; Mohammed Hussein Hamadi al-da (Mashhad University of Medical Sciences, 2024)
Background: There is a growing interest on the study and improvement of health-related quality of life (HRQOL). Type 1 diabetes can severely affect HRQOL. Iraqi adolescents with type 1 diabetes mellitus (T1DM) have lower quality of life (QOL) compared to their healthy peers.Aim: The present study was performed with aim to assess the effect of an empowerment program on the HRQOL of type 1 diabetes adolescents.Method: This clinical trial study was performed on162 adolescents with T1DM referred to the Al-Hassan Diabetes Center of Karbala/Iraq in 2021-2022. Firstly, the adolescents' Empowerment Package was compiled. Then sampling was taken via simple randomization method. The Kidscreen Questionnaire was used for data collection. The implementation of the empowerment program began for the intervention group in the groups of 10 to 15 people and in 10 sessions, three sessions per week. The control group received the routine care. Four weeks after completion of the intervention, the QOL score was again measured and compared in the two groups.Results: Before the intervention, there was no significant difference between the Kidscreen scores of the control (88.70±10.80) and intervention (87.89±9.50) groups (p=0.62), but this difference was significant in the post-intervention stage (82.90±8.00 vs 89.70±8.80) (p<0.001). In the inter-group comparison, paired t-test showed a significant difference in Kidscreen score before and after the intervention in the intervention group (p<0.001) and in the control group (p<0.001).Implications for Practice: We could suggest empowerment in diabetes self-care as a way to increase the QOL of adolescents with type 1 diabetes.